Data Quality of Nutritional Status among Children Using WHO Anthro Application: A Quasi-Experimental Study - Fauzia, Faurina Risca; Pangesti, Aldira (Jurnal Gizi dan Pangan, 2024)
This study aims to look at improving the quality of nutritional status data through WHO Anthro training in stunting focus areas. This study used a quasi-experimental quantitative method with a pretest-posttest equivalent repeated measures framework approach, using two groups. A total of 40 kindergarten teachers were sampled, divided equally into two groups. The control group was taught how to plot nutritional status using WHO charts and the intervention group was trained how to use the WHO Anthro application. Data was analyzed by non-parametrical means with a Friedman test to compare the pre-mid-post data in each group of different samples. The group trained by WHO Anthro showed that the data quality on nutritional status was significantly different, with a p=0.000. The evaluation conducted after two months of training proved to be significantly different in terms of information and data accuracy with p=0.030 and p=0.040, respectively. WHO Anthro is proven to be able to facilitate kindergarten teachers in determining the nutritional status of students, and the resulting nutritional status reports are of higher quality because they are more accurate and useful for early detection of stunting in each school.